Poziom zaawansowania zarządzania strategicznego a wielkość organizacji w świetle badań absolwentów SP PRE-MBA MiTM przy Wydziale Nauk Ekonomicznych SGGW - Pietrzak, Michał; Wojcieszkiewicz, Marta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
This paper try to identify the level of strategic management process in the Polish organizations and the scope of differences in this level accordingly to the size of organization. Research based on opinion of selected responders group shows that practices of strategic management differs from state of the art presented in the literature. Research shows also that these practices are more advanced in bigger organizations